Influence of Integration Processes on Modern Forms of a Clustering of Economy - Bilczak, Wasyl; Borodin, Aleksandr; Bilczak, Michał; Streltsova, Elena (Olsztyn Economic Journal, 2017)
In this article the authors analyze the theoretical aspects of the economy under the conditions of modern processes of integration. The authors describe the existing schools and concepts of integration. Modern studies focus on the evolution of integration processes, which has largely affected the key elements of the world economic mechanism. There are features and advantages of clusters in the context of strengthening regional integration. The factors of the regional economy, which contribute to the increased efficiency of clusters and the territory as a whole at the micro and macro levels, are determined. Also components of the strategy of cluster development are grounded.